Distal muscle weakness as the main onset symptom in thymoma-associated myasthenia gravis: a case report and literature review - Wu, Xuan; Xu, Xiao-tian; Zhou, Lin; Qiao, Kai; Zhao, Chong-bo; Luo, Su-shan (Frontiers in Immunology, 2025)
Myasthenia gravis (MG) is an autoimmune disorder within the spectrum of neuromuscular rare diseases, characterized by fluctuating muscle weakness. This report presents a case of a middle-aged woman with a chronic onset of asymmetric upper limb weakness accompanied by difficulty in finger extension, without ptosis or fluctuation for 4 years. The patient was finally diagnosed with MG by a significant decrement of Compound Muscle Action Potential in repetitive nerve stimuli, positive anti-acetylcholine receptor antibodies as well as the presence of a mass located in the anterior mediastinum. With subsequent immunotherapies for one month, the patient exhibited marked enhancement in muscle strength, followed by an uneventful thymectomy. After two months, the patient’s symptoms were fully alleviated, as evidenced by the reduction in Quantitative MG Score from 9 to 4 points, Myasthenia Gravis Composite Score from 6 to 1 points, Myasthenia Gravis Activities of Daily Living Score from 4 to 1 points, and Myasthenia Gravis Quality of Life-15 score from 14 to 8 points respectively. This case highlights the importance of differentiating autoimmune disorders from hereditary neuromuscular diseases and initiating timely treatment.